Molecular diagnosis of culture negative infective endocarditis: clinical validation in a group of surgically treated patients - Grijalva, M; Horváth, R; Dendis, M; Erný, J; Benedík, J (Heart (British Cardiac Society), 2003)
OBJECTIVE: To assess the clinical validity of polymerase chain reaction (PCR) based molecular methods in the microbiological diagnosis of culture negative infective endocarditis in a group of surgically treated patients. DESIGN: Retrospective case-control study. SETTING: Reference cardiovascular surgical centre. PATIENTS AND SAMPLES: 15 culture negative patients with infective endocarditis classified according to Duke criteria, with 17 heart valve samples; 13 age and sex matched control patients without infective endocarditis, with 13 valve samples. INTERVENTIONS: Medical records were reviewed and clinical, demographic, and microbiological data collected, including results of molecular detection of bacteria and fungi from valve samples. The clinical validity of molecular diagnosis was assessed, along with the sensitivity and speed of the systems. RESULTS: In the study group, 14 patients were PCR positive (93%). Organisms detected were streptococci (3), staphylococci (2), enterobacter (1), Tropheryma whippelii (1), Borrelia burgdorferi (1), Candida albicans (1), and Aspergillus species (2). Three cases were positive on universal bacterial detection but the pathogen could not be identified because of contaminating background. One case was negative. All but two positive cases showed clinical correlations. These two cases had no symptoms of infective endocarditis but there was agreement with the surgical findings. All control cases were PCR negative. Results were available within eight hours, and if sequencing was necessary, within 48 hours. CONCLUSIONS: PCR based molecular detection of pathogens in valve samples from surgically treated culture negative infective endocarditis patients is fast, sensitive, and reliable. The technology, combined with thorough validation and clinical interpretation, may be a promising tool for routine testing of infective endocarditis.
Keywords: Polymerase Chain Reaction; Aged; Retrospective Studies; Polymorphism, Restriction Fragment Length; lidé středního věku; senioři; polymerázová řetězová reakce; lidé; Adult; Middle Aged; dospělí; DNA bakterií; DNA, Bacterial; studie případů a kontrol; Female; bakteriální endokarditida; Male; ženské pohlaví; Case-Control Studies; Humans; mužské pohlaví; Endocarditis, Bacterial; polymorfismus délky restrikčních fragmentů; retrospektivní studie